The journey of the voices in the steps in back - Matos, Vanessa Soares (2013)
This study aims to analyze the storybook titled Os passos em volta (The steps around), of Herberto Helder, realizing narrative nodes between literary voices, the depicted notion of travel and questioning the issues of innocence and experience, which permeate the whole work. The study rises from the will of toss glances, not for poetry, however for the brief fiction of not only a poet, but also storyteller Herberto Helder, highlighting a slice of his literary output not so broadly known in Brazil. Thereby, the purpose is to defend that the tales feature narrative voices, at the same time, singular and plural, which are interconnected in the book in not random way, but rather, projecting senses. Besides, intends to understand the innocence and experience, not as a straight route, as it supposes, when get travel; but in a undulating and circular dynamic, impulsing the characters to the constant motion.